In-vitro release profile of anti-periodontitis doxycycline hyclate emulsion - Mohd Shafri, Mohd Affendi; Mohamed, Farahidah; Hamidon, Nurhani Emira; Adina, Anugerah Budipratama (2017)
Periodontitis, a biofilm infection affecting the gum and teeth, has a high prevalence and has no efficient treatment to date. In this study, doxycycline hyclate, a semi synthetic derivative of tetracycline was used as the active pharmaceutical ingredient (API) to formulate an anti-periodontitis emulsion. Different amount of lecithin and hydroxypropylmethylcellulose (HPMC), both acting as surfactants, were used in the formulations and tested for drug release profile. The in-vitro drug release profile was conducted using USP Apparatus 1 with PBS of pH 6.8 under sink condition. A predetermined time point h0was set up to take out the solution from the vessel for quantification. In order to quantify the in-vitro performance, a method validation was completed using UV-spectrophotometry following the requirements listed under ICH Q2 (R1) guidelines. A standard calibration curve with a good linearity, R2= 0.9973 was established. LOD and LOQ were in the range of 0.009 and 0.027 µg/mL respectively, whereas the slope of the standard curve was 0.051. The recovery rate for intra-day was from 98.27 to 101.39%, and from 100.85 to 102.57% for inter-day. The RSD was 1.6. It was found that lecithin-added formulation showsed complete drug release after 5 hours. In contrast, lecithin+HPMC-added formulation gave a total release after 2 hours. Thus, the lecithin-added formulation showed a slower release profile compared to the lecithin+HPMC-added formulation and may be the formulation of choice for future testings.